Flint - L'Amour, Louis (Bantam Books, 1960)
Flint left the West at the age of seventeen, leaving behind a rootless past and a bloody trail of violence. In the East he became one of the wealthiest financiers in America -- and one of the most feared and hated. Now, suffering from incurable cancer, he has come back to New Mexico to die alone. But when an all-out range war erupts, Flint chooses to help Nancy Kerrigan, a local rancher. A cold-eyed speculator is setting up the land swindle of a lifetime, and Buckdun, a notorious assassin, is there to back his play. Flint alone can help Nancy save her ranch ... with his cash, his connections -- and his gun. He still has his legendary will to fight. All he needs is a little time, and that's fast running out ..
55227
Keywords: Western; Women Ranchers